Strong fullerene and polycyclic aromatic hydrocarbon electron acceptors with perfluorinated substituents - San, Long K., author; Strauss, Steven H., advisor; Henry, Charles, committee member; Borch, Thomas, committee member; Szamel, Grzegorz, committee member; Wang, Qiang, committee member (Colorado State University. Libraries, 2015)
The world energy consumption is increasing at an alarming rate and only 10% comes from renewable energy resources. Harnessing the potential energy provided by the sun would provide enough energy to meet the world energy demands and more. One method to improve the collection of solar power is to provide materials that are lightweight, flexible, robust, and low manufacturing costs. The focus of this dissertation include the molecular design of novel materials to be used as organic semiconductors in a variety of applications such as organic photovoltaic and organic light emitting diodes. One very important aspect of these organic electronics is the electron acceptors employed in such devices. The need for strong electron acceptors and higher stabilities under thermal and oxidative stress were investigated by the perfluoroalkylation and perfluorobenzylation of fullerenes and polycyclic aromatic hydrocarbons. The first chapter of this dissertation demonstrates the novel fullerene derivative (nicknamed faux hawk) that possesses physicochemical properties suitable for use in organic photovoltaics. In fact, an organic photovoltaic figure of merit (ϕΣμ, yield of free charge carriers x sum of the charge carrier mobilities) determined from time resolved microwave conductivity measurements showed that faux hawk is comparable to that of the most studied fullerene electron acceptor, PCBM. Other properties are compared between faux hawk and PCBM. Mechanistic insight revealed, for the first time in fullerene chemistry, the formation of a carbon–carbon bond via a carbanion from the fullerene cage. The second chapter of this dissertation investigates novel polycyclic aromatic hydrocarbons containing fluorine withdrawing functional groups via perfluoroalkylation and, for the first time, perfluorobenzylation. These fluoromodifications have profound influences on the physicochemical and electronic properties that are all important for designing new electron acceptors. For example, the perfluorobenzylation greatly affects the π‐π intermolecular interactions and is more electron withdrawing than the trifluoromethyl group. Often times a bulky functional group is desired to promote certain properties (i.e., fluorescence). Several analytical methodologies including ¹⁹F and ¹H NMR spectroscopy, absorption and emission spectroscopy, mass spectrometry, cyclic voltammetry, gas-phase electron affinity, low-temperature photoelectron spectroscopy, X-ray diffraction, and DFT calculations are used to characterize the compounds discussed. These fundamental studies allow for future molecular engineering and design of even stronger electron acceptors. At the same time, the organic semiconductor library is expanding for use in optoelectronics.
Keywords: fluorinated; polycyclic aromatic hydrocarbon; fullerene; electron acceptors